Evaluasi Saluran Drainase di Perumahan Alam Sinar Sari Kabupaten Bogor Jawa Barat - Fahri Ekananda; Nora Herdiana Pandjaitan; Maulana Ibrahim Rau (Departemen Teknik Sipil dan Lingkungan, IPB University, 2019)
Drainage system is one of the important infrastructure components to drain runoff from rainfall. The purpose of this research were to identify the condition of existing drainage system in Alam Sinar Sari Residence, to analyze the discharge using EPA SWMM 5.1 application, and to analyze the suitability of existing drainage system with its runoff. The research was conducted since March 2018 on Alam Sinar Sari Residence which is located in Cibeureum Petir, with the total area of 15 ha. Based on analysis and statistic test, the acceptable distribution model is Log Pearson III model with 5 year return period. The rainfall designed was 175.86 mm. Based on simulation done using SWMM 5.1, the actual debit of conduit C76 were bigger than its planned debit and should be re-evaluated. Conduit C76 had dimension of depth of 0.31 m and width of 0.34 m. Based on simulation the discharge in C76 of 0.088 m3/s was bigger than the planned debit which was only 0.069 m3/s. After evaluation, conduit C76 should undergone changes of width dimension from 0.34 m to 0.50 m to be able to hold runoff.Keywords : designed rainfall, drainage, EPA SWMM 5.1, runoff